Investigating oral presentation anxiety of freshmen English major students in a Philippine higher educational institution - Docena, Vince Tristan; Buenaventura, Kent Harvey; Lobingco, Walter; Manlimos, Sheena; Joseph Nacionales, Joseph; Claridad, Norberto (Yayasan Mitra Persada Nusantara, 2023)
The objective of this Interpretative Phenomenological Analysis study is to gain a deeper understanding of how Freshmen English Major Students in a Philippine Higher Educational Institution experience and cope with anxiety related to oral presentations. Semi-structured interviews were carried out using a group of students who struggle with oral presentation anxiety. The interviews are recorded, transcribed, manually coded, and thematically examined. This qualitative study focuses on examining the students' perception of their anxiety, its causes, coping mechanisms, and its impact on their academic performance and well-being. The results reveal five themes for the encountered problems: (1) apprehension and distress in oral presentations (2) resource scarcity and readiness deficiency results to constrained engagement (3) the spotlight fears and trembling grip on stage (4) medium hurdles like encountering language disruptions and intrusions (5) the struggles with regards to one’s well-being; and six themes for the coping strategies: (1) emotional respite in human connections (2) mental resilience and adaptation (3) the calming rhythm for stress relief (4) harnessing movement and artistry for coping showcases embodied expressions (5) embracing emotional equilibrium through the power of acceptance in coping (6) unique coping strategy and perspective. The findings of this study add to a better understanding of the influence of this anxiety on student progress and assist in designing therapies to help this population's anxiety about oral presentations.